2022
DOI: 10.3389/fcimb.2022.803082
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Trimethylamine Oxide-Induced Model Implicates Gut Microbiota-Related Mechanisms in Frailty

Abstract: Frailty is a complicated syndrome that occurs at various ages, with highest incidence in aged populations, suggesting associations between the pathogenesis of frailty and age-related changes. Gut microbiota (GM) diversity and abundance change with age, accompanied by increased levels of trimethylamine oxide (TMAO), a systemic inflammation-inducing GM metabolite. Thus, we hypothesized that TMAO may be involved in the development of frailty. We successfully established and verified a novel model of frailty in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This study represents the inaugural comprehensive, large-scale MR analysis examining the genetic basis for a causal relationship between gut microbiota and the FI. Prior research on this association predominantly utilized clinical trials and animal studies ( Chen et al, 2022 ), which involved collecting and analyzing fecal samples from patients with frailty using 16S rRNA gene sequencing ( Jackson et al, 2016 ; Margiotta et al, 2020 ; Lauretani et al, 2021 ). However, these approaches often faced challenges due to confounding factors such as age and smoking habits, complicating the establishment of a direct causal link.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study represents the inaugural comprehensive, large-scale MR analysis examining the genetic basis for a causal relationship between gut microbiota and the FI. Prior research on this association predominantly utilized clinical trials and animal studies ( Chen et al, 2022 ), which involved collecting and analyzing fecal samples from patients with frailty using 16S rRNA gene sequencing ( Jackson et al, 2016 ; Margiotta et al, 2020 ; Lauretani et al, 2021 ). However, these approaches often faced challenges due to confounding factors such as age and smoking habits, complicating the establishment of a direct causal link.…”
Section: Discussionmentioning
confidence: 99%
“…The Clostridium innocum group , part of the Clostridium genus, consists of Gram-positive bacteria adapted to hypoxic or microaerobic conditions. An increase in Clostridium abundance correlates with higher levels of trimethylamine (TMA) ( Chen et al, 2022 ), which may contribute to an increased risk of frailty. In a recent investigation by Lim et al (2021) , they examined the correlation between gut microbiota and frailty in a cohort of 176 elderly Korean individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that TMAO can promote inflammatory hepatocellular carcinoma by inducing ROS and activating ILK/AKT/mammalian target of rapamycin (mTOR) signaling via POSTN[ 42 ]. Our previous studies showed that administration of TMAO produced a novel model of frailty in mice[ 43 ]. In this TMAO-induced frailty model, the abundance of Firmicutes was decreased slightly, while the abundance of Bacteroidetes was significantly increased in the gut.…”
Section: The Underlying Mechanism Of the Influence Of The Gm On Frail...mentioning
confidence: 99%